2023
DOI: 10.1038/s41598-023-48494-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3-(pyrazol-4-yl)-2-(1H-indole-3-carbonyl)acrylonitrile derivatives induce intrinsic and extrinsic apoptotic death mediated P53 in HCT116 colon carcinoma

Magda F. Mohamed,
Nada S. Ibrahim,
Amna A. Saddiq
et al.

Abstract: A novel series of α-cyano indolylchalcones was prepared, and their chemical structures were confirmed based on the different spectral data. Among them, compound 7f was observed to be the most effective bioactive chalcone with distinguished potency and selectivity against colorectal carcinoma (HCT116) with IC50 value (6.76 µg/mL) relative to the positive control (5 FU) (77.15 µg/mL). In a preliminary action study, the acrylonitrile chalcone 7f was found to enhance apoptotic action via different mechanisms like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Hybridization may lead to the development of anticancer drugs that are both safer and more potent than those now available on the market. , Furthermore, due to their extraordinary lipophilicity, hydrophobicity, ability to penetrate cell walls, and resistance to degradation, diaryl ether substructures are important in various medications and recently discovered agrochemicals. , They have been discovered to have a variety of bioactivities, including antiviral, anticancer, antibacterial, β-glucuronidase enzyme inhibitory action, radical scavenging, cytotoxicity, antitubercular, and antitubulin activity. Bis-heterocyclic compounds are among the popular scaffolds frequently found in drugs and pharmaceutically relevant substances because combining different heterocycle systems produces novel hybrid molecules that may be more biologically active than their separate components. There have been several reports of the antibacterial, anticancer, antiallergic, and other disease-fighting effects of bis-heterocycles. , Encouraged by the findings above and as part of our ongoing research interest in the synthesis of heterocycles and their bis-heterocyclic analogues, we present the design and synthesis of novel hybrid molecules composed of diphenyl ether linked to various heterocyclic systems. In this context, we recently investigated the Hantzsch reaction for the manufacture of bis-dihydropyridine and their corresponding fused derivatives based on diphenyl ether, and their antibacterial activity against various bacterial strains was evaluated .…”
Section: Introductionmentioning
confidence: 91%
“…Hybridization may lead to the development of anticancer drugs that are both safer and more potent than those now available on the market. , Furthermore, due to their extraordinary lipophilicity, hydrophobicity, ability to penetrate cell walls, and resistance to degradation, diaryl ether substructures are important in various medications and recently discovered agrochemicals. , They have been discovered to have a variety of bioactivities, including antiviral, anticancer, antibacterial, β-glucuronidase enzyme inhibitory action, radical scavenging, cytotoxicity, antitubercular, and antitubulin activity. Bis-heterocyclic compounds are among the popular scaffolds frequently found in drugs and pharmaceutically relevant substances because combining different heterocycle systems produces novel hybrid molecules that may be more biologically active than their separate components. There have been several reports of the antibacterial, anticancer, antiallergic, and other disease-fighting effects of bis-heterocycles. , Encouraged by the findings above and as part of our ongoing research interest in the synthesis of heterocycles and their bis-heterocyclic analogues, we present the design and synthesis of novel hybrid molecules composed of diphenyl ether linked to various heterocyclic systems. In this context, we recently investigated the Hantzsch reaction for the manufacture of bis-dihydropyridine and their corresponding fused derivatives based on diphenyl ether, and their antibacterial activity against various bacterial strains was evaluated .…”
Section: Introductionmentioning
confidence: 91%
“…In this area of research, we identified the chalcone derivative 1, as well as its structure-related synthetic analogs (2)(3)(4), all of which have a 3,4,5-trimethoxyphenyl B ring and display antiproliferative activity in several human tumor cell lines, and the growth inhibitory effect of these compounds is associated with mitotic interference [33,34] (Figure 1). Among chalcones with antitumor activity, α-substituted chalcones have proved to be quite active [35]. Particularly, the α-substitution of chalcones by alkyl groups represents a promising approach to obtain compounds with improved growth inhibitory activity in cancer cell lines through interference with microtubules [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Considering these findings and our continuous interest in developing heterocycles with improved pharmacophoric characteristics, we report the design and synthesis of new hybrid compounds that comprise thieno­[2,3- b ]­pyridines linked to piperazine or amide-containing moieties.…”
Section: Introductionmentioning
confidence: 99%